Screening for terminal drought stress tolerance in cowpea genotypes (Vigna unguiculata L.) - Moslem Fathi; Mohamadreza Bihamta; Naser Majnoon Hosseini; Aliakbar Shah Nejat Boushehry; Hadi Mohammad Ali Pour Yamchi (پژوهش‌های حبوبات ایران)
In order to study and determine the most effective traits, drought tolerance indices and identify tolerant genotypes in terminal drought stress on the cowpea, an experiment was carried out based on an augment design in two separate conditions in the Karaj Farm, Faculty of Agriculture, Tehran University in 2009. Drought stress was imposed by cutting irrigation after flowering against normal irrigation on 238 cowpea genotypes. Evaluation of studying genotypes under drought conditions was conducted using nine indices, including mean productivity (MP), Harmonic Mean (HARM), Tolerance Index (TOL), Stress Susceptibility index (SSI), Stress Tolerance index (STI), Geometric Mean productivity (GMP), Yield Index (YI), Yield Stability Index (YSI) and Yield Reduction percent (Yr). To determine the relationship between grain yield and indices, Pearson correlation coefficient was calculated. The MP, GMP, HARM and STI indices which have the most significant correlation with yield in stress and non-stress conditions were introduced as the best indices for screening tolerant genotypes to drought and high-yielding in both environmental conditions. Using Biplot scatter graph in 238 cowpea genotypes and according to genotypes status in Biplot scatter graph, 4, 149, 180, 6, 147, 151, 160, 55, 9 and 189 genotypes were identified as tolerant genotypes with high-yield. Cluster analysis based on investigating indices and yield under drought stress and non-stress conditions showed that genotypes was grouped in four clusters and most of drought tolerant genotypes with high yield were grouped in third cluster, while most of sensitive genotypes to drought stress were grouped in the second cluster.